2020
DOI: 10.1039/c9cp05405g
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the response of asymmetry in the hydrophobic chains of novel cationic lipids towards biological function

Abstract: Variations in molecular architecture of the hydrophobic tails of cationic lipids influence cationic liposome*s efficiency of delivering nucleic acids during cell transfection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…[23b] This corresponds to the higher average amplitude of the donorÀ acceptor distance fluctuations in the latter case than that of the former. The higher amplitude of the donorÀ acceptor distance fluctuations measured in terms of the half-width of the probability distribution curve is consistent with the possibility of system flexibility which manifests conformational relaxation of the model drug [38] at pre-micellar SDS during recognition to DNA. This conformational flexibility of the model drug at pre-micellar concentration of SDS assists in the delivery of TB to DNA, as discussed in the latter section.…”
Section: Chembiochemsupporting
confidence: 77%
“…[23b] This corresponds to the higher average amplitude of the donorÀ acceptor distance fluctuations in the latter case than that of the former. The higher amplitude of the donorÀ acceptor distance fluctuations measured in terms of the half-width of the probability distribution curve is consistent with the possibility of system flexibility which manifests conformational relaxation of the model drug [38] at pre-micellar SDS during recognition to DNA. This conformational flexibility of the model drug at pre-micellar concentration of SDS assists in the delivery of TB to DNA, as discussed in the latter section.…”
Section: Chembiochemsupporting
confidence: 77%
“…The molecular structures of cationic lipids are crucial to cell uptake, endosomal escape, and cytotoxicity. 18 , 146 , 147 , 148 , 149 Kolašinac et al. 95 reported that an inverted conical shape and an aromatic molecule in cationic lipid are indispensable to the fusion induction.…”
Section: Main Textmentioning
confidence: 99%
“…The molecular structures of cationic lipids are crucial to cell uptake, endosomal escape, and cytotoxicity. 18,[146][147][148][149] Kola sinac et al 95 reported that an inverted conical shape and an aromatic molecule in cationic lipid are indispensable to the fusion induction. Bruininks et al 16 elucidated the molecular effects of lipid tail saturation on lipid fusion and TE and suggested that cationic lipid tail saturation is a necessary condition for these processes.…”
Section: Factors Affecting the Therapeutic Efficacy Lipid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the development of chemical and biological experimental techniques Förster resonance energy transfer (FRET) plays a significant role. 1,2 Extreme spatial resolution (1–10 nm) in FRET lies on the nearfield optical communication where the radius of the interaction between two participating molecules (donor and acceptor) is much smaller than the wavelength of light emitted by the donor molecule. In the nearfield region, the emitted photons from the donor molecules, which are duly absorbed by the acceptor, are virtual in nature as their existence violates the conservation of energy and momentum, and hence FRET is known as a radiation-less mechanism.…”
Section: Introductionmentioning
confidence: 99%